Potential availability of cadaver organs for transplantation. Issue 6784 (4th May 1991) - Salih, M A; Harvey, I; Frankel, S; Coupe, D J; Webb, M; Cripps, H A
Abstract : OBJECTIVE--To determine the potential number of cadaver kidney donors by applying defined donor criteria to people dying in hospital. DESIGN--Prospective study of all deaths occurring in 21 hospitals from 1 September 1988 to 31 August 1989. Questionnaires were administered to medical and nursing staff and families of potential donors aged 1-69. SETTING--Acute care hospitals in Gwent, South Glamorgan, Mid Glamorgan, West Glamorgan, Pembrokeshire, and East Dyfed health authorities, serving a population of 2.2 million. MAIN OUTCOME MEASURES--Cause of death, age, ventilation at time of death, diagnosis of brain death, and consideration of consent. RESULTS--Adequate data were available for 9840 of 10, 095 hospital deaths (97.5% coverage). 188 patients aged 0-69 were identified as potential organ donors (widest definition), and of these 108 died without being ventilated at the time of death. Tests of brain stem death were formally completed in 57 cases, and organ donation was considered by the families of 47 of these potential donors. 26 patients became organ donors. Patients aged 50-69 with stroke were less likely to be ventilated than those aged less than or equal to 49 (21/96 v 24/34). Families of potential donors aged 20-39 were least likely to give permission. CONCLUSIONS--The supply of donor organs (specifically kidneys) could be increased by altering the management of patients aged 50-69 dying of severe cerebrovascular disease in general medical wards, in particular by increasing the proportion ventilated. The ethics of elective ventilation for the purposes of organ donation require discussion.